Filipino Science Teachers’ Needs, Challenges, and Practices in the New Normal - Tijap, Homobono Cabrera; Malamdag, Jerome Esco; Golla Paz, Princess Margaret; Orbase Pelgone, Alfons Jayson (FKIP Universitas Lampung, 2022)
This survey research involving 464 Filipino Science teachers determined the needs, challenges and practices in teaching and learning in the new normal. The collected data gathered showed that the science teachers needed (a) upskilling and reskilling in content-based knowledge and teaching strategies applicable to several identified challenging science topics in this new normal; (b) continuous training on the use of varied online platforms; (c) capacity building on the use of software and digital science activities applications; (d) a further enhancement in the following teaching related activities such as creating online assessments, online instructional modules, online class management, online teaching strategies, implementing online netiquette, and crafting the individual learning monitoring plan. The study further recommends rolling out this survey further in the Visayas and Mindanao regions and contextualize this survey for other content subject areas.Keywords: assessment, curriculum, instruction, new normal, science education.DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp123-151